Screening of Flavonoid Derivatives as Candidate Inhibitors For nsP2 Protease of Chikungunya Virus Using Molecular Docking - Faqih, Khoirul; Rong Cao; Saeed Ahmad (Tinta Emas Publisher, 2024)
This study focuses on the potential inhibition of nsP2 protease of chikungunya virus by flavonoid-derived compounds. Non-structural proteins, particularly the nsP2 protease, have an important role in chikungunya virus replication. Flavonoid-derived compounds were chosen as candidate inhibitors because they have previously been shown to be effective against other viruses such as influenza, herpes, and dengue fever. This study used molecular docking method to test six flavonoid groups, and four of them, namely hesperidin, rhoifolin, myricetin, and genistin, showed promising binding affinity. The molecular visualization results showed the occurrence of hydrophobic interactions and hydrogen bond formation. Hesperidin, as a flavanone, stood out as the most potential candidate with a binding affinity value of -9.4 kcal/mol. This study has implications for the development of potential inhibitors to inhibit chikungunya virus replication.